Unravelling polymorphism-driven luminescence in GFP chromophore analogues: insights into the phase transition and morphology-dependent optical waveguide properties - Dabke, Niteen B.; Raut, Yash; Mali, Bhupendra P.; Pandya, Rinu; Vanka, Kumar; Manoj, Kochunnoonny; Gonnade, Rajesh G. (Journal of Materials Chemistry C, 2024)
The advent of multi-emission organic solid-state materials in response to external stimuli has sparked the scientific community due to their potential application in developing sophisticated optoelectronic sensors and bioanalytical tools. This article presents green fluorescent protein chromophore (GFPc) analogue-based polymorphs exhibiting significantly different emissions due to various noncovalent interactions in the supramolecular environment and conformational alterations in the crystalline state. In both compounds (A and B), the polymorphs undergo monotropic thermal phase transitions that are characterized by DSC, HSM, and VT-PXRD techniques. The distinct fluorescent emission characteristics of these polymorphs demonstrated morphology-related optical waveguiding features. Specifically, the plate-type Form A1 emitted light with a 2D blue hue, while the needle-type Form A2 emitted light with a yellowish-green colour. Additionally, the impressive waveguiding capabilities of Form B1 were explored in both straight and singly/doubly bending configurations to facilitate fluorescence propagation. Consequently, there is significant interest in developing organic materials based on GFP chromophores, which exhibit low emission in solution but display multi-fluorescent emission in the solid state. These materials are promising for applications such as optoelectronic devices, security tags, live cell imaging, and fluorescent inks. Polymorphs of GFPc analogs A and B display differences in their optical waveguiding properties in 1D and 2D depending on the crystal shapes. Furthermore, Form B1 demonstrates efficient optical waveguiding capabilities even when the crystal is bent.

Unravelling the Cu-Co nanoparticle synergy over Ceria-Zirconia support toward efficient reverse water gas shift (RWGS) conversion under H2 lean conditions - Jagtap, Anuradha Vijay; Bamnia, Mahesh Kumar; Maibam, Ashakiran; Bajpai, Jyotsna Paliwal; Gupta, Sharad; Thomas, Sharon K.; Dabke, Niteen B.; Vinod, C. P. (Chemical Engineering Journal, 2025)
CO2 emissions leading to global warming and environmental and socio-economic issues have propelled the research community to develop technologies capable of capturing and converting CO2 into valuable products. Controlling the selectivity toward platform molecules like CO, methanol, or methane is a fundamental challenge in CO2 hydrogenation. Supported cobalt nanoparticles are known for hydrocarbon production through FischerTropsch (FT) reaction, and Cu-based catalysts are known for reverse water gas shift (RWGS) reaction. Here, we show that d-band centre can be carefully modulated by making bimetallic combinations of Cu and Co for a highly active RWGS catalyst. An oxygen vacancy-rich nanostructured ceria-zirconia (CZ) support with Cu nanoparticles (2 wt%) modified with as low as 0.05 wt% Co shows excellent conversion for CO2 hydrogenation and selectivity for CO below 500 degrees C. The optimized catalyst shows CO2 conversion even under hydrogen lean conditions (H2/ CO2 ratio 0.5:1), with a breakthrough rate of 206023 mmol/gmetal/h for CO at 600 degrees C, having H2 utilization of 80% for the RWGS process.
Keywords: Bimetallic catalyst; Ceria-zirconia; CO 2 hydrogenation; Cobalt catalyst; Copper catalyst; Reverse water gas shift (RWGS); synergistic effect